2004
DOI: 10.1111/j.0031-9317.2004.0285.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in strain and deposition of cuticle in developing sweet cherry fruit

Abstract: Changes in surface area, deposition and elastic strain of the cuticular membrane (CM) were monitored during development of sweet cherry (Prunus avium L.) fruit. Fruit mass and surface area ('Sam') increased in a sigmoidal pattern between 16 and 85 days after full bloom (DAFB) with maximum rates of 0.35 g day(-1) and 0.62 cm(2) day(-1), respectively. Rates of total area strain, namely the sum of elastic plus plastic strain, were highest in cheek and stem cavity regions followed by stylar and suture regions. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 14 publications
4
87
0
7
Order By: Relevance
“…Maguire et al (1999) and Curry (2009) reported similar observations. Roy et al (1994) and Knoche et al (2004) suggested that the microcracks occur on apple fruits as a result of their intensive growth and in particular the enlargement of their volume and surface area, while the mass of the cuticular membrane per fruit remains constant. The deepening of microcracks results from shrinkage of the fruits during storage, associated with water loss from their cells.…”
Section: Discussionmentioning
confidence: 99%
“…Maguire et al (1999) and Curry (2009) reported similar observations. Roy et al (1994) and Knoche et al (2004) suggested that the microcracks occur on apple fruits as a result of their intensive growth and in particular the enlargement of their volume and surface area, while the mass of the cuticular membrane per fruit remains constant. The deepening of microcracks results from shrinkage of the fruits during storage, associated with water loss from their cells.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include Prunus species and Vitis vinifera L. (Knoche et al, 2004;Becker and Knoche, 2012). As mentioned above, during cherry fruit growth there are two phases that involve a significant increase in fruit size and therefore expansion of the cuticle.…”
Section: Discussionmentioning
confidence: 99%
“…Cracking index is one of the most common laboratory tests that have been used to assess the degree of tolerance among cultivars avoiding the effect of environmental conditions (Christensen, 1972;Lane et al, 2000;Moing et al, 2004). Although differences in cracking tolerance levels have not been fully explained, a recent approach suggests that these could be related to the dynamics of the stages of fruit growth, with the properties of the cuticle being some of the most important factors involved in the onset of this problem (Knoche et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical performance of a fruit surface affects fruit appearance, handling and storage, but also plays a prominent role in fruit cracking. It is therefore not surprising that several studies were carried out to analyse fruit cracking symptoms of important crops such as tomato or sweet cherry (Prunus avium L.) fruit (Bargel et al 2004a(Bargel et al , 2004b and references therein; Knoche et al 2004). Only recently, Matas et al (2004b) reported a correlation between CM thickness, mechanical properties and resistance to cracking of cherry tomato fruit.…”
Section: Dynamics Of the Cuticle Mechanics During Fruit Ripeningmentioning
confidence: 99%